Mediation of Marketing Capabilities in Market Orientation, Entrepreneurial Marketing on Marketing Performance - Andari, Titiek Tjahja; Diposumarto, Ngadino Surip; Muharam, Hari (International Journal Labs, 2025)
Small businesses have become an important part of the Indonesian economy, but most of their performance has not been able to meet the growing demands of customers. This study aims to analyze the factors that can influence the marketing performance of small businesses in Bogor City using descriptive and verification methods. A survey of 350 respondents was conducted to determine a general description of the influence of market orientation, entrepreneurial marketing, and marketing capabilities on marketing performance, as well as the mediating role of marketing capabilities. Analysis of the influence between variables was conducted using the Structural Equation Modeling method, with data processed using Lissrel 10.2. The test results show that market orientation influences marketing capabilities, and entrepreneurial marketing influences marketing capabilities. The marketing capabilities of market orientation and entrepreneurial marketing influence marketing performance. Marketing capabilities can mediate the influence of market orientation on marketing performance and mediate some of the influence of entrepreneurial marketing on marketing performance. The novelty of this study is the discovery of a mediation relationship model of marketing capabilities in the influence of market orientation and entrepreneurial marketing on the resulting marketing performance.